Development of communication skills of students - Maxliyo Dilshodbekova Isroilovna (Zien Journals, 2022)
This article describes the psychological aspects of tutor-student cooperation in the educational process. Valuable scientific results were obtained due to the research of the influence of social-psychological, emotional-emotional, spiritual-cultural and territorial factors that form the relationship of tutor and student cooperation, ensure its effectiveness, negatively affect interpersonal relations and cooperation activities. and psychological analysis was carried out
Keywords: tutor; student; collaborative relationship; interpersonal relationship